Development of Learning Achievement and Problem-Solving Ability of Second Grade Students Using STEM Education - Tuanted, Nuttawadee; Chaiprasert, Pattaraporn; Singlop, Somsiri (Journal of Buddhist Education and Research (JBER), 2025)
The purposes of this research were 1) To study learning achievement before and after learning of STEM Education 2) To compare learning achievement with the 70 percent criteria 3) To study problem solving ability before and after learning STEM Education. The participants consisted of 24 second grade students from Ban Yang-En school in the second semester of the 2024 academic year using cluster sampling. The research instruments were STEM education lesson plan, achievement test, problem solving ability test. The data were analyzed by using the mean, standard deviation, t-test for dependent sample. The results of this research show that: 1) The post-test scores after learning with STEM Education were statistically significantly higher than the pre-test at the .05 level. 2) The post-test scores after learning with STEM Education were statistically significantly higher than the 70 percent criterion at the .05 level. 3) The post-test scores of problem-solving abilities through the use of STEM-based instructional design were statistically significantly higher than the pre-test at the .05 level.